Profil Representasi Matematis Siswa dalam Menyelesaikan Soal Lingkaran Ditinjau dari Self Efficacy - Nurhikma, Nurhikma; Alfisyahra, Alfisyahra; Lefrida, Rita; Pathuddin, Pathuddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to describe the mathematical representation of ninth grade students of Hidayatullah Palu Integral Junior High School in solving circle problems in terms of self-efficacy. This research method is descriptive qualitative research. Data collection is done by self efficacy questionnaire, written test, interview and documentation. Data validity uses member check, extended observation, and dependability. The results of this study indicate that subjects with high self efficacy can use all indicators of mathematical representation optimally, able to express their mathematical ideas in three representations namely visual representation, symbolic representation and verbal representation to solve problems from a problem. Students with moderate self efficacy can use all indicators of mathematical representation but not maximally. students with low self efficacy have not maximally fulfilled the indicators of visual mathematical representation ability and have not been able to fulfill the indicators of symbolic representation and verbal representation. Conclusion, students with high self efficacy have high representation skills, students with moderate self efficacy have moderate representation skills, and students with moderate self efficacy have moderate representation skills. with moderate self efficacy have moderate representation skills, and students with low self efficacy have high representation skills. students with low self efficacy have low representation ability. low. Keywords: Circles, Mathematical Representation, Self Efficacy